2022
DOI: 10.1038/s41598-022-11640-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of C-reactive protein increased levels and high disease activity are predictors of cardiovascular disease in patients with axial spondyloarthritis

Abstract: An accurate prediction of cardiovascular (CV) risk in patients with Axial Spondyloarthritis (axSpA) is a strong unmet need, as CV risk algorithms poorly perform in these subjects. The aim of this study was to establish whether the persistence of high C-reactive protein (CRP) and high disease activity may be considered predictive factors of CVD in axSpA. 295 patients without personal history of CVD, were consecutively enrolled in this study. To evaluate the relationship between CV events occurrence (fatal and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Of note, 40% of patients had to be reclassified to high-risk patients after plaques were recognized in carotid ultrasound [ 23 ]. In contrast, CV events are indeed associated with persisting elevation of CRP through clinical visits [ 25 ]. Also, radiographic progression of the spine is accompanied by raised markers of subclinical atherosclerosis [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, 40% of patients had to be reclassified to high-risk patients after plaques were recognized in carotid ultrasound [ 23 ]. In contrast, CV events are indeed associated with persisting elevation of CRP through clinical visits [ 25 ]. Also, radiographic progression of the spine is accompanied by raised markers of subclinical atherosclerosis [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in contrast to our data, treatment persistence in that registry study was higher in bDMARD naïve (87%) than in previously TNFi-treated patients (68%). Another Italian study of 34 PsA patients treated with ustekinumab after failure or inadequate response to csDMARDs or TNFi reported achievement of MDA -in 70.5% of subjects at month 24 (24), and maintenance of low or minimal disease activity status has been recently shown to have a great influence on patients' quality of life and perception of their clinical condition (27).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study from Spain found that CRP > 3 mg/L and ESR at the time of diagnosis were significantly associated with CIMT, a surrogate marker of atherosclerosis [81]. Another study from Italy showed that the persistence of increased CRP levels and high disease activity (BASDAI > 4 or ASDAS > 2.1) are associated with increased CVD [82].…”
Section: Inflammation and (Subclinical) Cardiovascular Diseasementioning
confidence: 99%